MACROACCOUNTING AND SOME OF ITS BASIC PROBLEMS. - Yu, S. C. (The Accounting Review, 1957)
Abstract The two terms, microaccounting and macroaccounting, are created mainly for the purpose of recognizing the extent of the progress of accounting today. The term macroaccounting has the advantage over others in identifying explicitly the area to which accounting is applied. Macroaccounting is still expanding and the discussion of its six major branches in this paper is by no means exhaustive. Macroaccounting may be studied at two levels, business macroaccounting and economic macroaccounting. It is obvious that in this paper efforts have mostly been devoted to the former. Eventually, a set of conventions, assumptions, and standards for macroaccounting will be developed as in microaccounting. It is also suggested that most of the principles and standards of microaccounting may be applied to macroaccounting with modifications and additions. In examining the various branches of macroaccounting, one must note that the development of a national balance sheet has lagged behind in a manner that tends to cripple the entire system of macroaccounting. Another major task is to integrate the several branches of macroaccounting regarding classifications of accounts and systems of recording transactions. Only in this way can the full usefulness of macro- accounting be reached. The problem of the valuation basis is a complex one. No single method can answer all the questions. No matter what valuation bases are selected, the principles of consistency and comparability should be strictly observed. The need for offering macroaccounting courses in accounting departments was also suggested.